P4_2 A Flashy Outfit - Rowe, Ryan; Byworth, Kayleigh; Garner, James; Lawrence-Morgan, Dennis (Physics Special Topics, 2022)
This paper explored the effect Flash's speed would have on the appearance of his uniform. It used the relativistic Doppler effect to analyse the change in colour of his uniform. It was found that when the Flash travelled at 0.9c he would only be visible 78^° θ 121^° and 239^° θ < 283^° in the x axis. It was also found that the Flash would at times be a source of UV-C photons.